Additional faunistic records of Protosternini from China (Coleoptera: Hydrophilidae: Sphaeridiinae) - Mai, Zu-Qi; Jia, Feng-Long (Zootaxa, 2026)
Two species of the Oriental endemic tribe Protosternini Hansen, 1991 (Coleoptera: Hydrophilidae: Sphaeridiinae), Protosternum arunvallense Hebauer, 2002 and Rhombosternum birmanense J. Balfour-Browne, 1942, are reported from China for the first time. Protosternum arunvallense is the third known species of the genus Protosternum Sharp, 1890 in China, while R. birmanense is the first record of the genus Rhombosternum J. Balfour-Browne, 1942 for the country. Both species are diagnosed and illustrated based on Chinese specimens. An identification key to the Chinese species of Protosternini is provided.